(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2021)
Project -based learning (PBL) is a student-centered teaching approach that organizes learning around projects. It increases students’ motivation to learn and prepares them for the 21st century classroom demands through developing real-world experience. The purpose of this study is to explore the benefits of project-based learning on students’ in a Malaysian secondary school. This is a qualitative case study. The sample consists of 3 teachers’ from a secondary school in Malaysia. Semi-structured interviews were conducted with the participants. The collected data were coded and analyzed using thematic analysis. The study revealed that the participants perceived PBL as a beneficial teaching approach that has the potential to increase student-teachers’ engagement and help them understand more deeply the subject content through self-learning and learning by doing. The advantages of using PBL discussed by the participants were improved lecturer-student and student-lecturer relationships, skill development and real-world practice. The results of this research show that student-teachers’ understand PBL from both positive and negative perspectives. It is considered that findings of this study would improve students-teachers’ motivation and equip them with the necessary skills to successfully implement PBL.